Hydrological features of Ljig municipality - Kovačević-Majkić Jelena (Zbornik Radova: Geografski institut "Jovan Cvijić", 2006)
Ljig municipality has a dense hydrographic network, composed mostly of the streams within the Ljig River basin. However, the quantities of water in these streams are relatively small, and characterized by great irregularities during the year. Moreover, in the last ten years of the research period, there has been a noticeable decrease of water quantities. The most significant river in the area is the Ljig River (48.9 km long), which is the largest tributary of the Kolubara River. The spring of the Ljig River is situated within the territory of the municipality, while the length of the stream on this territory is 30.13 km. The most significant tributaries of Ljig are Kacer, together with its tributary Kozeljica, as well as Dragobilj with Dragobiljica (Lalinacka Reka), Zerevac and Godevac. Among all the springs in Ljig municipality, the most important is the karst spring in the village of Ba, which is considered as the main spring of the Ljig River. It is used for water-supply of the town of Ljig and the village Kadina Luka. There are many water-management problems in Ljig municipality. The most prominent are the problems of erosion, gulling streams and floods, water-supply issues, as well as insufficient water-management infrastructure.